2019
DOI: 10.1002/cld.801
|View full text |Cite|
|
Sign up to set email alerts
|

Locoregional Therapy for Hepatocellular Carcinoma: Transarterial Chemoembolization Versus Transarterial Radioembolization Versus Stereotactic Body Radiotherapy†

Abstract: The use of locoregional therapy (LRT) has various potential roles in the treatment of hepatocellular carcinoma (HCC.) It is important to determine what the intended goal of LRT is prior to receipt of LRT. The choice of one form of therapy over another is often dictated by center preference and more importantly experience. This article will review the various forms of LRT that are often used in the treatment of HCC. BriDGe/DOWn-sTaGinG TO liver TransPlanTTransarterial chemoembolization (TACE) is the most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In addition, Currie et al [ 41 ] also reported that TACE alone combined with interventional chemoembolization and radiotherapy could reduce normal liver tissue damage, improve tumor control rate and prolong patient survival time. Also, TACE combined with radiotherapy was significantly better than TACE alone in reducing recurrence rate and metastasis rate[ 42 ]. The above study further confirmed the conclusion of this study that compared with TACE alone, TACE combined with TARE could have a better therapeutic effect and clinical value with better safety for patients with advanced HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Currie et al [ 41 ] also reported that TACE alone combined with interventional chemoembolization and radiotherapy could reduce normal liver tissue damage, improve tumor control rate and prolong patient survival time. Also, TACE combined with radiotherapy was significantly better than TACE alone in reducing recurrence rate and metastasis rate[ 42 ]. The above study further confirmed the conclusion of this study that compared with TACE alone, TACE combined with TARE could have a better therapeutic effect and clinical value with better safety for patients with advanced HCC.…”
Section: Discussionmentioning
confidence: 99%